Populist Wave in Nepalese Politics: Communitarianism, Republic Citizenship, Utility and Personalization of Politics - Humagain, Sanjeev (Journal of Political Science, 2025)
While populism is a recurring feature in Nepali politics, it has received limited academic scrutiny, particularly regarding its connection to the rise of left-wing movements. This paper investigates contemporary populism in Nepal, a subject primarily overlooked by academic research despite its prevalence in the political arena. Based on contextual analysis and conceptual generalization approach, this study examines the macrostructural conditions and demand perspective of populist politics in contemporary Nepal. The study draws the conclusion based on secondary data. Along with data and statistics from policy documents, reports and newspapers, this study focuses on political development since 2017 – mainly focusing on coalition politics, relations between leaders of political parties and their members, and political cooperation and competition. Indeed, the speeches of the political leaders and their gestures are important data for the analysis. Departing from prior assumptions regarding its relationship with the left, this study argues that Nepali populism i increasingly assumes a right-wing character. This is evident in two phenomena: a dominant political discourse prioritizing the ‘common good’ and a balancing of order and freedom, a shift from liberal citizenship commitments established in the Constitution of 2015 and earlier political accords ("populism as discourse"). Additionally, political actors predominantly engage in utility-based justifications for their actions, marginalizing ideological influences and personalizing politics ("populism as a political strategy"). These trends collectively signify a movement toward right-wing populism within the country.